Determinación de las propiedades físicas y químicas del lote número 14 campus Salache mediante el uso de técnicas básicas del laboratorio de suelos 2023-2024. - Chiliquinga Claudio, Valeria Alexandra (2024)
The agricultural sector is experiencing problems of increasing soil desertification, which has led to losses in production processes, in addition to a lack of knowledge of the characteristics of soils and their poor management. This research project was carried out in the Soil Laboratory of the Technical University of Cotopaxi. The objective was to determine the physical and Chemical properties of the soil of a Silvo-pastoral system on the Salache Campus using nine basic laboratory techniques, which helps to strengthen the knowledge of small and medium-sized producers. The zig-zag type of sampling was used to collect six samples where the apparent density, real density, pH, catión exchange, organic matter, porosity, structure and nutrients were analysed by means of saturated paste extraction. To corrobórate the data obtained with the methodologies used, one sample was sent to the INIAP laboratory. From the results obtained it was determined that the soil of the Silvopastoral system has a soil structure of 1.96 moderately stable, real density 2.60 g/cm3, apparent density of 1.20 g/cm3, porosity of 50%, pH of 8.40, catión exchange capacity of 23 meq/100 gr, an organic matter of 0.41 % Na 153ppm, Ca 123, K 88meq/100g, a texture of 62% sand, 29% silt, 9% clay and a texture of sandy loam were found, which are mostly corroborated with the data obtained from the INIAP analysis. It was established that the use of the nine proposed techniques does determine real valúes of the physical and Chemical parameters of the soil.